Distribution and pollution assessment of trace metals in seawater and sediment in Laizhou Bay - 吕冬伟 郑冰 房燕 申格 刘惠军 (Chinese journal of oceanology and limnology, 2015)
Selected trace metals (Pb, Cd, Cu, Hg) and arsenic in seawater and surface sediments of Laizhou Bay were determined, to evaluate their spatial distribution, pollution risk and potential ecological risk. Concentrations of the elements were 0.56–2.07, 0.14–0.38, 12.70–18.40, 0.014–0.094, and 1.13–2.37 μg/L in the seawater and 8.94–32.2, 0.18–0.67, 4.51–30.5, 0.006–0.058, and 5.75–15.3 mg/kg in sediments for Pb, Cd, Cu, Hg and As, respectively. High concentrations of the trace metals and arsenic in seawater and surface sediments were generally observed near the river estuary. The pollution risk result of the elements showed that Cu was the prominent trace metal pollutant in seawater, followed by Hg, Pb, Cd and As. The metal complex pollution index in seawater was at a medium level. The most important trace metal pollutant in sediments was Cd, followed by As, Cu, Pb, and Hg. Our pollution assessment suggests that trace metal pollution in Laizhou Bay sediments was at a low level. The potential ecological risk was also low in surface sediment.